2012
DOI: 10.5152/akd.2012.063
|View full text |Cite
|
Sign up to set email alerts
|

An observational study of the effect of coronary artery disease severity on acute pacing threshold and lead impedance in patients with permanent pacemaker

Abstract: An observational study of the effect of coronary artery disease severity on acute pacing threshold and lead impedance in patients with permanent pacemaker Kalıcı pacemaker'lı olgularda koroner arter hastalığı ciddiyetinin akut uyarı eşiği ve lead empedansı üzerine etkisini araştıran gözlemsel bir çalışma Original Investigation Özgün Araşt›rma ABSTRACTObjective: This study investigated the effect of coronary artery disease (CAD) severity, distribution and left ventricular ejection fraction (LVEF) on acute vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…This relation however was only observed when the ventricular lead was placed in the right ventricle (RV) apex, not in the RV outflow tract. Another study performed on 130 patients with a pacemaker or implantable cardioverter-defibrillator (ICD) revealed no associations between pacing parameters (lead impedance and pacing threshold) and distribution of LVEF or coronary artery disease, although the mean lead impedance was lower and mean pacing threshold was higher in the ICD patients than in pacemaker patients [11] . Pacing parameters might also be modified by proliferative scarring within the myocardium -the study by Vurgun et al showed that patients with proliferative scars in the right ventricle had a significantly higher pacing threshold compared with the control group matched by sex, age and lead type [12] .…”
Section: Discussionmentioning
confidence: 99%
“…This relation however was only observed when the ventricular lead was placed in the right ventricle (RV) apex, not in the RV outflow tract. Another study performed on 130 patients with a pacemaker or implantable cardioverter-defibrillator (ICD) revealed no associations between pacing parameters (lead impedance and pacing threshold) and distribution of LVEF or coronary artery disease, although the mean lead impedance was lower and mean pacing threshold was higher in the ICD patients than in pacemaker patients [11] . Pacing parameters might also be modified by proliferative scarring within the myocardium -the study by Vurgun et al showed that patients with proliferative scars in the right ventricle had a significantly higher pacing threshold compared with the control group matched by sex, age and lead type [12] .…”
Section: Discussionmentioning
confidence: 99%